2015
DOI: 10.1371/journal.pone.0127218
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Morphological Change in the Masticatory Structures of an Important Ecosystem Service Provider

Abstract: Humans have altered the biotic and abiotic environmental conditions of most organisms. In some cases, such as intensive agriculture, an organism’s entire ecosystem is converted to novel conditions. Thus, it is striking that some species continue to thrive under such conditions. The prairie deer mouse (Peromyscus maniculatus bairdii) is an example of such an organism, and so we sought to understand what role evolutionary adaptation played in the success of this species, with particular interest in adaptations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
0
15
0
2
Order By: Relevance
“…La alteración y pérdida del hábitat natural por acción de diferentes actividades humanas y el establecimiento de sistemas productivos, genera impactos negativos sobre la diversidad biológica y abundancia de las especies (Saunders et al 1991, Santos & Telleira 2006. Estas condiciones pueden generar cambios en la dinámica de los ecosistemas, estructura trófica y procesos ecológicos, con posibles implicaciones en la preferencia del hábitat de los organismos (Aguirre et al 2002, Fahrig 2003, Arias 2008, Mena 2010, Doudna & Danielson 2015. De este modo, el ambiente puede influir en la morfología de los organismos a través de factores ambientales como la ubicación geográfica, la estructura del hábitat, la amplitud de la dieta y la repartición de los recursos, entre otros, actuando como medio de presión selectiva buscando probablemente reducir la competencia entre los individuos (Ricklefs & Miles 1994, Mancina & Balseiro 2010, Medeiros et al 2018.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…La alteración y pérdida del hábitat natural por acción de diferentes actividades humanas y el establecimiento de sistemas productivos, genera impactos negativos sobre la diversidad biológica y abundancia de las especies (Saunders et al 1991, Santos & Telleira 2006. Estas condiciones pueden generar cambios en la dinámica de los ecosistemas, estructura trófica y procesos ecológicos, con posibles implicaciones en la preferencia del hábitat de los organismos (Aguirre et al 2002, Fahrig 2003, Arias 2008, Mena 2010, Doudna & Danielson 2015. De este modo, el ambiente puede influir en la morfología de los organismos a través de factores ambientales como la ubicación geográfica, la estructura del hábitat, la amplitud de la dieta y la repartición de los recursos, entre otros, actuando como medio de presión selectiva buscando probablemente reducir la competencia entre los individuos (Ricklefs & Miles 1994, Mancina & Balseiro 2010, Medeiros et al 2018.…”
Section: Introductionunclassified
“…relacionados con la capacidad de forrajeo y el uso de hábitat de los murciélagos (Lee et al 2012). Sin embargo, para los murciélagos no existen investigaciones que han buscado entender la relación entre la morfología y la alteración del paisaje relacionados al establecimiento de sistemas agropecuarios, como si se ha hecho en grupos como peces y roedores (Palkovacs et al 2012, Doudna & Danielson 2015.…”
unclassified
“…However, a number of studies have demonstrated that shape can also undergo change in a short period of time (e.g. Nargosen & Cardini, 2009; Franssen, 2011; Yazdi & Adriaens, 2011; Doudna and Danielson, 2015). The size and shape changes resulting from such rapid evolution on islands or in habitat fragments have been shown to have measurable functional consequences, particularly with regard to feeding biomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the accessibility of these collections, there have been numerous calls for their digitization (i.e., capturing specimen-level data and specimen images into digital form) Large-scale digitization of herbarium specimens: Development and usage of an automated, high-throughput conveyor system research on global change (e.g., Lavoie, 2013;Vellend & al., 2013;Davis & al., 2015;Harsch & HilleRisLambers, 2016), evolution (e.g., Doudna & Danielson, 2015;Davis Rabosky & al., 2016), and conservation (e.g., Greve & al., 2016), to name a few.…”
Section: Introductionmentioning
confidence: 99%